The rules in Rylands v. Fletcher in Malaysia / Hapriza Ashari - Ashari, Hapriza (Faculty of Law, 1986)
A person is generally liable in tort when an act is done i) intentionally (for example trespass) or ii) negligently, In some cases, however, a person may be liable when he acts neither intentionally or negligently. In this instances the law has imposed a strict limit, a person's activities, and if this limit is exceeded the defendant is strictly or absolutely liable. The most Common Law example of such liability is known as the rule is Rylands v. Fletcher. The rule was propounded by Blackburn J. which was later approved by the House of Lords and now regarded as detinitive "We think that the true rule of law is, that a person who for his own purposes brings on his lands and collects and keeps there anything likely to do mischief if it escape, must keep it in at his peril, and if he does not do so, is prima facie answerable for all the damage which is the natural consequence of its escape. He can excuse himself by showing that the escape was owing to the plaintiff's default; or perhaps that the escape was the consequence of a vis major, or the Act of God. But as nothing of this sort exists here, it is unnecessary to inquire what excuse would be sufficient. The rule in Rylands v Fletcher will thus be applied where there had been a "non-natural uses of land" in that something has been introduced on the defendant's land which was not there naturally. This "something" might be water, gas, electricity, plants which have been artificially sown, or indeed anything which is naturally on land will of course, not make the owner of the land liable to pay damages except where the escape was done so negligence. The "escape" referred to in the rule must be the escape of the unnatural thing brought from the defendant's land to the plaintiff's land. Meaning that there must be an escape of the thing which inflicts the injury from a place over which the defendant has occupation or control to a place which is outside his occupation or control. The requirement that proof of escape is necessary means that only a person who suffers damage by reason of the dangerous thing crossing the boundry of the land from which it comes can succeed in an action. But it should be noted that the rule is confined to claims between neighbouring, occupiers of land.